تقييم التأثير الوقائي للمستخلص المائي لقشور الرمان على السمية الكبدية المستحثة بواسطة نتريت الصوديوم في ذكور السمان (Journal of Academic Research, 2026)
This study aimed to investigate the preventive and therapeutic effects of pomegranate peel extract against the toxic effects of sodium nitrite on the liver of male quails. A total of 24 male quails were used in this study and divided into six groups. The first group served as the control group and was administered distilled water at a dose of 1 ml/kg. The second group received sodium nitrite at a dose of 30 mg/kg. The third group was given pomegranate peel extract at a dose of 300 mg/kg. The fourth group  received pomegranate peel extract at a dose of 300 mg/kg in combination with sodium nitrite at a dose of 30 mg/kg.The experiment lasted for 30 days, after which liver samples were collected for histological examination. The results of the present study showed histopathological changes in the liver tissues of the sodium nitrite–treated group, including severe dilation and congestion of the central vein, the presence of inflammatory cells within the dilated sinusoids, moderate disintegration of the portal tracts, and intracellular edema. In contrast, the groups treated with pomegranate peel extract in combination with sodium nitrite exhibited noticeable improvement in liver tissue structure compared with the sodium nitrite group. Based on the obtained results, it can be concluded that pomegranate peel extract has an effective role in reducing the toxic effects of sodium nitrite on liver tissues in male quails.